Peran Aplikasi Discord Untuk Membangun Komunikasi Interpersonal Relation Grup Fervency Pada Game Perfect World II Indonesia - Wijaya, Safrial Angra; Suprihatin (DIGICOM : Jurnal Komunikasi dan Media, 2024)
The presence of the internet as a communication medium provides users with the convenience to communicate and interact with other internet users. Communication can occur anywhere, whether directly or indirectly. Through the Discord application, individuals can communicate by joining the Fervency Discord group, which is used for communication while playing the game Perfect World II Indonesia. Discord offers several ways to communicate, such as typing or speaking with other members by entering channels available within the Discord group. In the Fervency group, Discord users also build various interpersonal relationships similar to those in the real world, ranging from sharing personal life experiences to discussing work. This study aims to examine how Discord users build interpersonal relationships among players of Perfect World II Indonesia. The research method used is qualitative, based on data from interviews conducted with members of the Fervency group. From the eight Discord users interviewed, the researcher found that the role of the Discord application in building interpersonal relationships within the Fervency group offers various benefits in playing Perfect World II Indonesia, including features and ease of communication. Players are very active and always strive to communicate effectively to contribute to the team by providing or receiving information in the form of gameplay strategies through chat features, whether voice messages, text, or symbols.